URGENSI WAJIB BELAJAR 9 TAHUN UNTUK MASYARAKAT DI KAMPUNG PASIR BUNGUR DESA RANCASENGGANG KECAMATAN SINDANGKERTA KABUPATEN BANDUNG BARAT - Komarudin (LPPM STAI Darul Falah, 2024)
This research aims is to describe the urgency of 9 years of compulsory education for the society in Pasir Bungur Village. The method employed was qualitative method by using descriptive analysis. Data collection was the form of observation, interview, and documentation based on the researcher's scientific considerations. The research employed triangulation (observation, interview, and documentation) to increase the credibility of the research’s results. The results of the research showed that there were 5 obstacles inhibited factors in the realization of the 9 years compulsory education program for the society in Kampung Pasir, there were; (1) Low educational qualifications of parents; (2) low family economic capacity; (3) the location of the school is far from where the society live; (4) lack of public transportation that can take students to school locations; and (5) social environment. The efforts made by the researchers were to make an attempt to socialize it through the closing of Community Service Students (KKN) ceremony namely group 8 which was attended by the local community and the village government.